2011
DOI: 10.1186/1475-2875-10-75
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of molecular markers of anti-malarial drug resistance in Plasmodium vivax and Plasmodium falciparum in two districts of Nepal

Abstract: BackgroundSulphadoxine-pyrimethamine (SP) and chloroquine (CQ) have been used in treatment of falciparum and vivax malaria in Nepal. Recently, resistance to both drugs have necessitated a change towards artemisinin combination therapy (ACT) against Plasmodium falciparum in highly endemic areas. However, SP is still used against P. falciparum infections in low endemic areas while CQ is used in suspected cases in areas with lack of diagnostic facilities. This study examines the prevalence of molecular markers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 44 publications
(69 reference statements)
5
23
1
Order By: Relevance
“…Our observation corroborates the previous reports from Pakistan, Nepal, and Sudan. [39][40][41] However, no triple/quadruple mutations were detected, which is in contrast with previous findings from India 16,36 as India has different degrees of malaria endemicity, and the levels of mutations from the different geographical state is also varied. 42 With regard to the Pvdhps gene, majority of our isolates (77.2%) carried wild type alleles and frequency of single mutant (383G) and double mutant genotypes (383G/553G) was 10.2% and 12.6%, respectively, which have been found to be directly related to sulphadoxine resistance 43 and associated with reduced sensitivity to both sulfa drugs and sulfones.…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation corroborates the previous reports from Pakistan, Nepal, and Sudan. [39][40][41] However, no triple/quadruple mutations were detected, which is in contrast with previous findings from India 16,36 as India has different degrees of malaria endemicity, and the levels of mutations from the different geographical state is also varied. 42 With regard to the Pvdhps gene, majority of our isolates (77.2%) carried wild type alleles and frequency of single mutant (383G) and double mutant genotypes (383G/553G) was 10.2% and 12.6%, respectively, which have been found to be directly related to sulphadoxine resistance 43 and associated with reduced sensitivity to both sulfa drugs and sulfones.…”
Section: Discussioncontrasting
confidence: 99%
“…Pyrimethamine resistance has been investigated in a number of different geographical regions and strong evidence exists that F57L/I (TT A / A T A ), S58R (AG A ), T61M (A T G), S117N/T (A A C/A C C) and I173L/F ( C TT/ T TT) SNPs are responsible for resistance in P. vivax (Hawkins et al, 2007). Subsequent work has consistently shown that F57L/I (TT A / A T A ), S58R (AG A ), S117N/T (A A C/A C C) single mutations and S58R (AG A ) /S117N/T (A A C/A C C) double mutations are widely distributed in different geographical regions of south Asia (Auliff et al, 2006; Brega et al, 2004; de Pecoulas et al, 1998; Hastings et al, 2005; Imwong et al, 2003; Kaur et al, 2006; Kuesap et al, 2011; Lu et al, 2012; Mint Lekweiry et al, 2012; Ranjitkar et al, 2011; Schunk et al, 2006). Previous studies in Pakistan have shown that the S58R (AG A )/S117N (A A C) double mutation and S117N (A A C) single mutation conferring pyrimethamine resistance were present in different cities of the Punjab, Sindh and KPK provinces (Khattak et al, 2013; Zakeri et al, 2011).…”
Section: Discussionmentioning
confidence: 95%
“…Suwanarusk et al [24] studying the same gene, found that CQ IC50 was significantly higher in P. vivax isolates carrying the Y976F mutation than in isolates with the wild-type allele. Ranjitkar et al [25] found that the low resistance to CQ was due to the low prevalence of mutation Y976F in pvmdr1 (5%). However, most studies did not find any association between mutation in the pvmdr-1 gene and CQ-resistance corroborating these results [16,21,26,27].…”
Section: Discussionmentioning
confidence: 99%